2018
DOI: 10.1055/s-0038-1632403
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Treatments for Lymphedema

Abstract: Although nonoperative and operative treatments for lymphedema (LE) are well established, these procedures typically provide only partial relief from limb swelling, functional impairment, and the risk of cellulitis. The lack of a cure for LE, however, is due to an incomplete understanding of the underlying pathophysiological mechanisms, and current research efforts are focusing on elucidating these processes to provide new, targeted therapies for this prevalent disease for which there is no cure. This article r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…While these procedures reduce swelling by an average of 25–46%, decrease symptom burden, lessen risk of progression to chronic LE, improve function and cosmesis, and decrease amount of time spent daily on therapy, they do not usually eliminate the need for daily maintenance therapy, such as bandaging [ 102 , 103 , 104 , 105 , 106 ]. Remarkably, though, LVB and VLNT patients experience significantly decreased cellulitis incidence following surgery [ 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Because of the variable reductions in limb swelling and the continued need for daily maintenance therapy, use of the microsurgeries in LE patients remains controversial.…”
Section: Diagnostic Imaging Of Dysfunctional Lymphatics For Staginmentioning
confidence: 99%
See 1 more Smart Citation
“…While these procedures reduce swelling by an average of 25–46%, decrease symptom burden, lessen risk of progression to chronic LE, improve function and cosmesis, and decrease amount of time spent daily on therapy, they do not usually eliminate the need for daily maintenance therapy, such as bandaging [ 102 , 103 , 104 , 105 , 106 ]. Remarkably, though, LVB and VLNT patients experience significantly decreased cellulitis incidence following surgery [ 105 , 106 , 107 , 108 , 109 , 110 , 111 ]. Because of the variable reductions in limb swelling and the continued need for daily maintenance therapy, use of the microsurgeries in LE patients remains controversial.…”
Section: Diagnostic Imaging Of Dysfunctional Lymphatics For Staginmentioning
confidence: 99%
“…Because of the variable reductions in limb swelling and the continued need for daily maintenance therapy, use of the microsurgeries in LE patients remains controversial. In general, like conventional treatments, lymphovascular surgery is most effective when performed in earlier stages of LE, while there is still capacity for recovery of the lymphatic system [ 106 ]. Studies using ICG lymphography suggest that subjects with minimal dermal backflow are excellent candidates for lymphovascular surgeries.…”
Section: Diagnostic Imaging Of Dysfunctional Lymphatics For Staginmentioning
confidence: 99%
“…A more stable and powerful method than using a single fixed time point for quantifying the long-term survival benefit was previously published in this journal. 2 This approach involves comparing the tail areas of survival curves-the larger, the better. For instance, one may calculate the areas between 12 months and 36 months of follow-up in Figure 2A.…”
Section: Quantifying the Long-term Survival Benefit Of Pembrolizumab ...mentioning
confidence: 99%
“…Acquired lymphedema is a complex disease caused by cancer treatment or parasitic infection and few effective treatments are available for lymphedema. 1 , 2 , 3 It is urgently needed to develop new experimental approaches and therapeutic strategies. 3 In this study, we address a new role and mechanism of MSC‐ex (human umbilical cord Wharton's jelly mesenchymal stem cells derived exosome) in lymphedema treatment.…”
Section: Figurementioning
confidence: 99%
“… 1 , 2 , 3 It is urgently needed to develop new experimental approaches and therapeutic strategies. 3 In this study, we address a new role and mechanism of MSC‐ex (human umbilical cord Wharton's jelly mesenchymal stem cells derived exosome) in lymphedema treatment. We found that MSC‐ex delivered Ang‐2 (angiopoietin‐2) promoted lymphangiogenesis by upregulating Prox1 (Prospero Homeobox 1) mediated Akt signaling.…”
Section: Figurementioning
confidence: 99%